Phylogeography and connectivity of the Pseudocalanus (Copepoda: Calanoida) species complex in the eastern North Pacific and the Pacific Arctic Region - Questel, Jennifer Marie (J Plankton Res, 2016)
The genus Pseudocalanus (Copepoda, Calanoida) is among the most numerically dominant copepods in eastern North Pacific and Pacific-Arctic waters. We compared population connectivity and phylogeography based on DNA sequence variation for a portion of the mitochondrial cytochrome oxidase I gene for four Pseudocalanus species with differing biogeographical ranges within these ocean regions. Genetic analyses were linked to characterization of biological and physical environmental variables for each sampled region. Haplotype diversity was higher for the temperate species (Pseudocalanus mimus and Pseudocalanus newmani) than for the Arctic species (Pseudocalanus acuspes and Pseudocalanus minutus). Genetic differentiation among populations at regional scales was observed for all species, except P. minutus. The program Migrate-N tested the likelihood of alternative models of directional gene flow between sampled populations in relation to oceanographic features. Model results estimated predominantly northward gene flow from the Gulf of Alaska to the Beaufort Sea for P. newmani. Model scenarios that allowed bidirectional gene flow between sampled populations gave the best Bayesian predictions for P. acuspes, P. mimus and P. minutus. Under current warming trends, biogeographical boundaries and barriers for Pseudocalanus species may shift, allowing habitat range expansion or contraction and resulting in altered population connectivity between Arctic and sub-Arctic populations.